2022
DOI: 10.26502/acbr.50170312ee
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Covid-19 and Lockdown on Mental Health: Depression, Anxiety, Stress and Fear among Adult Population in Turkey

Abstract: Background: Most of the documented literature to date has reported that the COVID-19 pandemic is associated with greater distress, anxiety, anger, stress, and agitation among the general public compared to before the onset of the pandemic. Method and study design:A review was done to now the evidence for the antiviral and immunemodulatory properties of micronutrients. A search was done in PubMed, Scopus, and Google Scholar for the nutrients with proven effect against viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This evidence confirmed again that COVID-19 infection negatively impacts the quality of life and lifestyle of adults with T2DM as well as their general clinical outcome. Comparing COVID-19 patients with and without T2DM, we confirmed that the comorbid infections were characterized by higher levels of stress, fear, depression, and anxiety (from the DASS-21), and these results are in line with a wide body of evidence from the international literature regarding the mental health consequences of COVID-19 [16][17][18][19][20][21]. Specifically, the rate of depression, distress and sleep disorders in our group of patients affected by COVID-19 infection and T2DM was 25%, which is a bit lower than those found in similar studies reporting significant mental health issues in 43% of comorbid patients (with sleep disorders affecting 77% of the assessed patients) [25].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This evidence confirmed again that COVID-19 infection negatively impacts the quality of life and lifestyle of adults with T2DM as well as their general clinical outcome. Comparing COVID-19 patients with and without T2DM, we confirmed that the comorbid infections were characterized by higher levels of stress, fear, depression, and anxiety (from the DASS-21), and these results are in line with a wide body of evidence from the international literature regarding the mental health consequences of COVID-19 [16][17][18][19][20][21]. Specifically, the rate of depression, distress and sleep disorders in our group of patients affected by COVID-19 infection and T2DM was 25%, which is a bit lower than those found in similar studies reporting significant mental health issues in 43% of comorbid patients (with sleep disorders affecting 77% of the assessed patients) [25].…”
Section: Discussionsupporting
confidence: 84%
“…It has been also found that the clinical condition T2DM is highly associated with depression, anxiety, and stress symptoms over the course of illness. This comorbidity is due to the psychological adjustment of patients in the long term and some indirect consequences of metabolic dysfunctions over time (e.g., the impact of diabetes on the central nervous system) [16][17][18][19][20][21]. According to recent evidence, 33% of patients with T2DM report depressive symptoms, 11.2-26.3% report anxiety, and 39% report sleep disorders (also due to their obesity or obstructive sleep apnea) [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since poor sleep quality is linked to many medical and psychological disorders including obesity, cardiovascular diseases, and depression, and has a direct effect on life quality, investigating these effects of sleep quality is important (5)(6)(7)(8). Several neurocognitive dysfunctions such as attention deficits and cognitive performance impairment, as well as psychological disorders such as stress, depression, anxiety, and impulse control problems, are related to sleep disturbances (5,9). If untreated, such sleep-related deficits may lead to further potentially health-threatening consequences such as increased risk of cardiovascular diseases (4).…”
Section: Introductionmentioning
confidence: 99%